Developing practical wireless applications - Gratton, Dean A. (Elsevier Digital Press, 2007)
In a constant stream of new ideas, wireless technologies continue to emerge offering a range of capabilities, each affording simplicity and ease-of-use. Such diversity and choice should surely beg the question, are manufacturers using the right technology for the right product? Developing Practical Wireless Applications will explore this question and, in doing so, will illustrate many of the wireless technologies currently available whilst drawing upon their individual strengths and weaknesses. More specifically, the book will draw your attention to the diverse collection of standardized and proprietary solutions available to manufacturers. As developers and innovators your choices are not restricted to any norm and, as such, a standardized or proprietary solution may afford you greater benefits in realising any product roadmap. Developing Practical Wireless Applications will provide you with a comprehensive understanding of how each technology works, coupled with an exploration into overlapping, complementary and competing technologies. In establishing this foundation, we will explore wireless applications in their context and address their suitability. In contrast, the book also considers the practicality of a wireless world in an attempt to better understand our audience and specific demographic groups. Coupled with a richer understanding of our consumers, along with our technology make-up we can indeed target wireless products more effectively. *Explores techniques used to attack wireless networks including WarXing, WarChalking, BlueJacking, and BlueSnarfing *Discusses applications utilizing ZigBee, NFC, RFID, Ultra-Wideband and WirelessUSB (WiMedia) *Details Bluetooth 2.x +EDR and introduces the v3.0 (BToverUWB) specification *Includes fundamental introductions to WiFi, namely 802.11i, 802.11p and 802.11n *Compares personal-area and wide-area communications including 3G, HSDPA, 4G, and WiMAX, as well as introducing Wireless Convergence.